PERAN INTERLEUKIN 6 DALAM MENENTUKAN KELUARAN MODIFIED RANKIN SCALE PADA STROKE ISKEMIK AKUT - Winda Kusumaningrum, Salim Harris, Al Rasyid, Joedo Prihartono (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION STROKE IS ONE OF THE LEADING CAUSES OF DEATH AND DISABILITY THROUGHOUT THE WORLD AND HAS A HUGE IMPACT BOTH CLINICALLY AND SOCIOECONOMICALLY IN ACUTE ISCHEMIC STROKE THERE IS AN INCREASE IN IL6 LEVELS THAT WERE CORRELATED WITH MORE SEVERE NEUROLOGICAL DEFICITS MORE EXTENSIVE BRAIN DAMAGE AND WORSE PROGNOSES THEREFORE IL6 CAN BE USED AS AN EARLY SCREENING FOR THE IDENTIFICATION OF ACUTE ISCHEMIC STROKE PATIENTS WHO HAVE A HIGH RISK OF PROGRESSION OF NEUROLOGICAL DEFICITS AND HIGHER MORTALITY RATES